Dielectric and piezoelectric properties of PZT-cement composites - Chaipanich A. (2014)
Lead zirconate titanate (PZT) and cement composites of 0-3 connectivity were produced using PZT of 30-90% by volume. The effects of PZT on dielectric and piezoelectric properties of the composites were then investigated. The dielectric constant (εr) of the composites was found to increase with increasing PZT content. The εr value of 90% PZT composite obtained was 291 which is noticeably higher than that of PC sample (εr = 79). The dielectric loss (tan δ) was found to decrease with PZT content and the tan δ value was lowest at 0.63 for 90% PZT composite. Piezoelectric coefficient (d33) was found to increase with PZT content as expected. However, the effects were most significant at two stages, first at 30% PZT volume content (14 pC/N) and then at very high PZT content (90% by volume) where d33 value reached 43 pC/N. © 2006 Elsevier B.V. All rights reserved.